Surface Modification of Titanium and Titanium Alloys: Technologies, Developments, and Future Interests - Zhang, Lai-Chang; Chen, Liang-Yu; Wang, Liqiang (Advanced engineering materials, 2020)
Thanks to a considerable number of fascinating properties, titanium (Ti) and Ti alloys play important roles in a variety of industrial sectors. However, Ti and Ti alloys could not satisfy all industrial requirements; the degradation of Ti and Ti alloys always commences on their surfaces in service, which declines the performances of Ti workpieces. Therefore, with aim to further improve their mechanical, corrosion and biological properties, surface modification is often required for Ti and Ti alloys. This article reviews the technologies and recent developments of surface‐modification methods with respect to Ti and Ti alloys, including mechanical, physical, chemical, and biochemical technologies. Conventional methods have limited improvement in the properties and/or restriction on the geometry of workpieces. Therefore, many advanced surface‐modification technologies have emerged in recent decades. New methods make Ti and Ti alloys have better performance and extended applications. With requirement of high surface properties in future. Understanding the mechanism in various surface‐modification methods, combining the advantages of current technologies and developing new coating materials with high performance are required urgently. As such, incorporation of different surface‐modification technologies with high‐performance modified layers may be the mainstream of surface modifications for Ti and Ti alloys. The technologies and recent development of surface‐modification methods for titanium (Ti) and Ti alloys are reviewed. Such technologies have expanded the applications of Ti and Ti alloys in the past and present due to their enhanced surface properties. Likewise, the mainstream of surface modifications for Ti and Ti alloys in the future is also discussed.